Perbaikan Aspek Produksi, Manajemen dan Hukum Kelompok UMKM “Tuty Collections” - Saefullah, Encep; Mukhlis, Ahmad; Hifni, Mohammad (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The problems of the target partners of the "Tuty Collections" MSME group include that the production process is still done manually, so the products produced are not yet standardized, product designs and models do not have many variations, the number of sewing machines they own is still insufficient, thus affecting the amount of production produced, knowledge and skills Partner human resources in business management are still minimal, they do not have legal business operations, partner skills in marketing are still minimal and sales methods are still conventional, not using digital media, so it is difficult for sales volume to increase. Using the chronological method, the implementation of this activity resulted in an increase in the number of production and sales of partner products by 75% and the legal legality of business operations in the form of NIB was obtained.